Invasion of the body snatchers [videorecording (DVD)] - Siegel, Don, 1912-1991; McCarthy, Kevin, 1914-2010; Wynter, Dana; Finney, Jack (Silver screen classics., 2002)
Plant-like extraterrestrials have invaded Santa Mira, a small town in California, replicating the villagers in giant seed "pods" and taking possession of their souls while they sleep. In a terrifying race for his life, Dr. Miles Bennell escapes to warn the world of the deadly invasion of the pod people.